Association between ultra-processed food consumption and the nutrient profile of the Colombian diet in 2005 (2019)
ABSTRACT: To evaluate the consumption of ultra-processed food and drink products and its association with the nutrient profile of the Colombian diet in 2005. Materials and methods. Food consumption based on 24-hour dietary records from 38 643 men and women was classified into four NOVA groups according to the extent and purpose of food processing. Results. Ultra-processed food and drink products represented 15.9% of the total energy daily intake, compared to 63.3% from minimally processed food, 15.8% from processed culinary ingredients, and 4.9% from processed food. Non-ultra-processed food items had a healthier nutritional profile compared to ultra-processed items in terms of contribution to total calories from protein, carbohydrates, total fat, saturated fat, free sugar, fiber and energy density. Conclusions. Ultra processed food products have a less healthy nutrient profile than non-ultra-processed ones. An increase in the consumption of these foods must be prevented within Colombia.